Keberlanjutan Permukiman Rawa Desa Baru di Kabupaten Hulu Sungai Utara Kalimantan Selatan - Chaidir, Ahmad; Murtini, Titien Woro (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
As the traditional village, Desa Baru has a value and local wisdom which is represented by spatial planning and environmental management. In terms of environmental management, the social behavior of local people in Desa Baru strengthens the existence of resided activity. However, the resided activity in Desa Baru conducted by local people can't be revealed as sustainable activity unless an assessment of sustainability has been conducted. Thus, the researcher is eager to examine the sustainability of swamp settlement area in Desa Baru: "How is the sustainability assessment of swamp settlement area in Desa Baru, Kecamatan Danau Panggang, Kabupaten Hulu Sungai Utara?" Referring to the objectives of study, the analysis has been conducted in several dimensions namely economic, socio culture, ecology, infrastructure and institutional dimension. The research used kuantitative method. All dimensions have been analyzed by Multi Dimensional Scalling (MDS). Each attribute uses scoring method in order to determine the sustainability. Moreover, the scoring result has been analyzed by using Rapfish Software resulting sustainability status. According to the analysis result, sustainability status the sustainability of swamp settlement area in Desa Baru can be categorized as "sustainable enough" since the percentage of sustainability resulted by MDS is 57,76%.